2022
DOI: 10.1101/2022.03.28.486133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An ALS-associated KIF5A mutant forms oligomers and aggregates and induces neuronal toxicity

Abstract: KIF5A is a kinesin superfamily motor protein that transport various cargos in neurons. Mutations in Kif5a cause familial amyotrophic lateral sclerosis (ALS). These ALS mutations are in the intron of Kif5a and induce missplicing of KIF5A mRNA, leading to splicing out of exon 27. Exon 27 of KIF5A encodes a cargo-binding tail domain of KIF5A; therefore, it has been suggested ALS is caused by loss of function of KIF5A. However, precise mechanisms how mutations in KIF5A cause ALS remain to be clarified. Here, we sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…We expressed mScarlet-fused KIF5A(∆exon27) in cells and stained them with recombinant H2 mAb. KIF5A(∆exon27) formed aggregates in the cytoplasm as described previously (Fig 2G) (Nakano et al, 2022;Pant et al, 2022). Immunofluorescence microscopy showed that the recombinant H2 mAb recognized the KIF5A(∆exon27) aggregates in cells (Fig 2H and I).…”
Section: Use Of Recombinant H2supporting
confidence: 82%
“…We expressed mScarlet-fused KIF5A(∆exon27) in cells and stained them with recombinant H2 mAb. KIF5A(∆exon27) formed aggregates in the cytoplasm as described previously (Fig 2G) (Nakano et al, 2022;Pant et al, 2022). Immunofluorescence microscopy showed that the recombinant H2 mAb recognized the KIF5A(∆exon27) aggregates in cells (Fig 2H and I).…”
Section: Use Of Recombinant H2supporting
confidence: 82%
“…While our manuscript was under review, two independent groups further supported that DExon27 causes neuronal toxicity through gain-of-function in different cellular and animal systems (Baron et al, 2022;Nakano et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…It may also be the case that inactive motors can associate directly with membranous cargo (66), in prime position for cargo adaptor-driven activation at the right place and time. Recent studies showing that amyotrophic lateral sclerosis (ALS)-linked mutations in KIF5A disrupt autoinhibition underscore the broad pathophysiological significance of these questions (67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%